Flood Susceptibility Mapping in Ambon City - Helwend, Joseba Kristina; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2022)
Flood can be defined as the inundation or flow of water that cannot be contained and exceeds normal limits, resulting in damage to the environment and humans. An area is considered prone to floods if it experiences high rainfall intensity, has low soil capacity or saturated soil, impermeable surfaces, degraded forest conditions, and steep slopes in the upstream area. By using Geographic Information System (GIS), existing data and information can be integrated, and modeling can be easily conducted. Moreover, the tendency of rainfall patterns and the possibility of flooding can be analyzed. Therefore, predictions for flood occurrences and the resulting damages can be promptly determined. Ambon city is an area with a topography that includes flat land, hills, and steep slopes with gradients exceeding 20%. This condition allows the city's development to occupy flat areas, leading to a relatively high population density. On the other hand, limited flat land forces the population to settle on the outskirts of the city, including the slopes of hills and riverbanks.